(3GdJHQ GdeSHhc aj Pjd GdSdhcs - (3eMeO Hf YHO GdQMef Hf eMeO, TeS GdOjf GdSNGhj , J (B902 (3g` s; (3GdebQjRj , Jbj GdOjf CHh GdYHGS,J (B845 (3g` s ((3efRd eDdag s)
(3ChdgG (B:s
(3SfI (B851 s
(3BNQgG (B:s
(3SfI (B853 (3ef faS GdfSNI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B11s
Keywords: (3GdJGQjNs